The Relationship of Authoritarian Parenting with Social Anxiety in College Students - Yisya Malika Areva; Hadi Abdillah; Ernawati Hamidah (Jurnal Keperawatan Priority, 2025)
College students are in early adulthood, a developmental stage vulnerable to psychological pressure, including social anxiety. One of the contributing factors to this condition is authoritarian parenting, which is typically characterized by strict control, lack of open communication, and high parental expectations. These traits can negatively affect an individual’s mental health. This study employed a quantitative research design with a cross-sectional and correlational approach. A total of 75 undergraduate nursing students at Universitas Muhammadiyah Sukabumi were selected using purposive sampling. Data were collected through the Parenting Styles and Dimensions Questionnaire (PSDQ) and the Hamilton Anxiety Rating Scale (HARS), and analyzed using the Chi-Square test. The results revealed that 65.3% of the respondents experienced authoritarian parenting, and most reported moderate to severe levels of social anxiety. Statistical analysis indicated a significant relationship between authoritarian parenting and social anxiety among students (p = 0.001). Authoritarian parenting was positively correlated with social anxiety levels. The higher the authoritarian style in parenting, the higher the level of social anxiety experienced by the students. This study highlights the importance of balanced parenting approaches and emotional support to minimize the risk of social anxiety disorders among college students.